Optional Materials of the Printed Liturgiarion [in the Light of Selected Examples from the Kyiv Metropolitanate in the 16th and 17th Century] - Nowak, Alicja Z. (Poznańskie Studia Slawistyczne, 2018)
In 16th–17th-century’s liturgical books one can find numerous additions regarded as redundant and optional. These paratextual elements are: verbal (e.g., prefaces, dedicational verses or letters, afterwords, introductions), iconic (schemas, illustrations) and both combined. Unnecessary materials in printed liturgiarions apart from the above-mentioned are: teachings of Jan Chrysostom, Basil the Great and Gregory Dialogos – the authors of Divine Liturgy and the short eulogistic compositions about Church Fathers, sometimes accompanied by their images. These additional elements are great evidence of development of liturgical practice, documents certifying intellectual level of Ruthenian clergy and renovating ambitions of hierarchy. For this reason, they should be widely considered as worthy sources in the study about religion reform in the Metropolitanate of Kiev and of a church culture in old Polish-Lithuanian Commonwealth.